Phenotypic Characterization of Human Monocytes following Macronutrient Intake in Healthy Humans - Alshahrani, Awad; Bin Khunayfir, Abdalmalik; Al Rayih, Mohammed; Al Sayed, Hasan; Alsadoon, Abdullah; Al Dubayee, Mohammed; Zahra, Mahmoud; Alrumayyan, Yousof; Al Zayer, Maha; Nasr, Amre; Aljada, Ahmad (Frontiers in Immunology, 2017)
Background: Three subsets of human monocytes in circulation have been identified and their characterization is still ill-defined. Although glucose and lipid intakes have been demonstrated to exert pro-inflammatory effects on mononuclear cells (MNCs) of healthy subjects, characterization of monocytes phenotypes following macronutrient (glucose, protein, and lipid) intake in humans remains to be determined. Methods: Thirty-six healthy, normal weight volunteers were recruited in the study. Subjects were randomly assigned into three groups, each group consisting of 12 participants. Each group drank equal calories (300 kcal) of either glucose or lipids or Whey proteins. Each subject served as his own control by drinking 300 mL of water 1 week before or after the caloric intake. Baseline blood samples were drawn at 0, 1, 2 and 3-hour intervals post caloric or water intakes. MNCs were isolated, and the expression levels of different cluster of differentiation (CD) markers (CD86, CD11c, CD169, CD206, CD163, CD36, CD68, CD11b, CD16, and CD14) and IL-6 were measured by RT-qPCR. Results: Equicaloric intake of either glucose or lipids or Whey proteins resulted in different monocyte phenotypes as demonstrated by changes in the expression levels of CD and polarization markers. Whey proteins intake resulted in significant mRNA upregulation in MNCs of CD68 and CD11b at 1, 2, and 3 hrs post intake while mRNA of IL-6 was significantly inhibited at 1 hr. Lipids intake, on the other hand, resulted in mRNA upregulation of CD11b at 2 and 3 hrs and CD206 at 1, 2 and 3 hrs. There were no significant changes in the other CD markers measured (CD86, CD163, CD169, CD36, CD16 and CD14) following either Whey proteins or lipids intakes. Glucose intake did not alter mRNA expression of any marker tested except CD206 at 3 hrs. Conclusions: Macronutrient intake alter the expression levels of polarization markers in MNCs of human subjects. A distinct population of different monocytes phenotypes may result in human circulation following the intake of different macronutrients. Further studies are required to characterize the immunomodulatory effects of macronutrients intake on monocytes phenotypes and their characteristics in humans.